DOCUMENTATION AND SIGNIFICANCE OF TECTONIC EVENTS IN THE NORTHERN TABAS BLOCK (EAST-CENTRAL IRAN) DURING THE MIDDLE AND LATE JURASSIC - KAZEM SEYED-EMAMI; FRANZ T. FÜRSICH; MARKUS WILMSEN (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
Apart from global sea-level fluctuations, the sedimentary pattern of the northern Tabas Block during the Middle and Late Jurassic was mainly governed by tectonic events of varying intensity and areal extent. These events took place during the Middle Bajocian (mid-Cimmerian tectonic phase), Early Bathonian, Late Bathonian, Early Callovian, Late Oxfordian, and Late Kimmeridgian. The importance and extent of each event and its influence on the facies pattern of the northern Tabas Block is briefly discussed and demostrated by some examples.